(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the weight loss in patients treated with mandibular fracture at tertiary care hospital. Study Design: A descriptive study Place and Duration of Study: This study was conducted at the Department of Oral and Maxillofacial Surgery, Jinnah Post Graduate Medical Centre, Karachi, from September 2023 to March 2024. Methods: A validate questionnaire was selected to record the patient’s demographic data like age, gender, socio economic status, residential status and level of education. Also history and outcome were inquired like smoking, etiology of fracture, fixation of mandibular with or without IMF and weight loss (Yes/No). Effect modifiers like age, gender, socio economic status, residential status, etiology of fracture and type of fixation with or without IMF were controlled by stratification. Post stratification chi-square test or fisher exact test was applied to see their effect on the presence of weight loss. P value equal or less than 0.05 was considered as significant. Results: In our study, majority of cases were treated without intermaxillary fixation (IMF) 47 (65.3 %) while 25 (34.7 %) with IMF. Mean base line weight of our study cases 70.08 ± 11.14 kg, after 4 weeks weight 68.0 ± 10.90 kg and mean weight loss 2.07 ± 0.94 kg were noted. Of these 72 cases, the weight loss was noted in 23 (31.9 %). Conclusion: High frequency of weight loss was noted in patients who were treated with or without intermaxillary fixation (IMF). Weight losses in our patients were significantly associated with increasing age.